Makna Simbolis dan Filosofi di Balik Gerakan Tari Tradisional Indonesia - Oktavianus, Oktavianus; Citrawati, A A I A; Nurmalena, Nurmalena; Fakhrizal, Herwan (Universitas Lampung, 2024)
This study aims to examine the symbolism and philosophy in traditional Indonesian dance movements and their role in conveying social and spiritual values. Using a literature review approach, this research collects and analyzes relevant literature published between 2015 and 2024, including indexed international journals, books, and scholarly articles. Thematic analysis and content analysis are used to identify the main themes in the dance movements, such as harmony, unity, and the relationship between humans, nature, and God. The results show that traditional Indonesian dance is more than just a performing art; it serves as an important medium for transmitting profound moral values and life philosophies, such as self-control, cooperation, and inner peace. These findings highlight the need to preserve the symbolism and philosophy of traditional dance amidst globalization and modernization. The implementation of these findings can be carried out by integrating these cultural values into arts and culture education, both in formal and non-formal settings, to ensure that the younger generation not only masters dance techniques but also understands the philosophical meanings contained within them. This study provides deep insights into the importance of maintaining the relevance of traditional dance as part of the nation’s cultural identity.Keywords: Dance Philosophy, Social Values, Cultural Preservation, Symbolism, Traditional Indonesian Dance